COMPARASION OF SERUM HOMOCYSTEINE LEVELS IN PRIMIGRAVIDAS DURING SECOND AND THIRD TRIMESTERS OF NORMAL PREGNANCY AND PREECLAMPSIA - Taimoor, Alruba; Buland, Khalid; Nazir, Aamir; Qureshi, Sadaf Anwar (Pakistan Armed Forces Medical Journal, 2019)
Objective: To determine and compare serum homocysteine (Hcy) levels in primigravidas in second and third trimesters of normal pregnancy and preeclampsia.Study Design: Cross-sectional comparative study.Place and Duration of Study: Study was conducted at department of Gynecology and Obstetrics, Lahore General Hospital, from June 2013 to May 2014.Material and Methods: One hundred primigravida patients of normal pregnancy and preeclampsia of second and third trimester were evaluated in terms of parameters including blood pressure and Hcy. The subjects were further subdivided into four groups. Age of patients was ranging from 18 to 40 years.Results: The age of selected hundred subjects ranged from 18 to 40 years, while the mean ± SD age was 25.92 ± 5.56 years. Systolic blood pressure ranged from 100 to 210 mmHg, (mean ± SD 136.3 ± 24.623 mmHg). The recorded diastolic blood pressure ranged from 70 to 130 mmHg, (mean ± SD 87.8 ± 15.736 mmHg). There was a significant difference in Hcy amongst pre-eclamptics and controls of 2nd and 3rd trimesters and also betweencontrols of 2nd and 3rd trimesters and cases of both 2nd and 3rd trimesters (p